Polymorphisms in Estrogen Receptor-Α and -Β Genes and Their Correlations with Risk Factors in Iranian Breast Cancer Patients - Abbasi, Sakineh (2009)

(untitled)
Receptor-mediated estrogen activation participates in the development and progression of breast cancer. Evidence suggests that alterations in estrogen signaling pathways, including estrogen receptor-α (ER-α) and estrogen receptor-β (ER-β) occur during breast cancer development. Estrogen receptor genes (ERs) polymorphism has been found to be associated with breast cancer and clinical features of the disease in Caucasians. In order to investigate whether polymorphisms in the ER-α and ER-β are associated with breast cancer risk in a case-control study was conducted with 150 Iranian patients newly diagnosed invasive Breast Ductal Carcinoma, and 147 healthy women. PCR single-strand conformation polymorphism method and direct sequencing screened the selected encoding regions exon 4 ER genes for mutation or variant sites were performed. Three silent single nucleotide polymorphisms (SNPs) were found in the ER- α gene (exon 1, exon 4, exon 8 respectively), as reported previously in other studies, but at significantly different frequencies and one SNP was found in ER- β gene (exon 7). The statistical significance was achieved in the most of demographic characteristics. Age at menarche of less than or equal to twelve years old in codon 594 of ER- α gene and among the eight different races the race of Fars in all four polymorphic sites of ER-α and ER-β genes were revealed statistically significant differences between case and control groups (p=< 0.05). Furthermore, blood group B of all four ABO blood groups, was shown statistically significant differences between case and control groups (p=< 0.05) for all four polymorphic sites of codons 10, 325, 594 of ER-α and 392 in ER-β . The frequency of allele 1 in codon 594 exon 8 was significantly higher in breast cancer patients (48.0%) than in control individuals (1.4%; P = 0.001). The codon 392 polymorphisms were presented only in cases group, in genotypes of heterozygote with statistically significant frequency of 8.7% and in the genotypes of homozygote with statistically significant frequency of 1.3%. Furthermore, in 1he exon 4 we found a novel mutation at codon 323 in Iranian women, and the statistical significance was achieved for the presence and absence of LN metastases at this codon (P = 0.017). Combination of the three SNP markers in ER-α may increase the incidence of age at menarche of less than or equal twelve years old, which itself could increase accuracy in predicting developing breast cancer later in their lifetime. Moreover, SNP in codon 392 of ER-β gene is more effective than those SNPs in three polymorphic sites of ER-α gene, in developing familial breast cancer and LN metastases phenotype. This was the first systematic association study in ER-α and ER-β genes polymorphisms and demographic characteristics for breast cancer risk in Iran. In conclusion, our data suggest that ER- α and ER-β genes polymorphisms are correlated with various aspects of breast cancer risk in Iranian women. Moreover, the greater the frequency of allele 1 in codon 10, codon 325 and codon 392 the lesser the likelihood of LN metastasis in the Iranian breast cancer patients. We also noted that greater the frequency of allele 1 in codon 10 in the form of 01, the more likely in patients with familial breast cancer. Our findings suggest that, SNP in codon 392 of estrogen receptor- β gene is much effective than those SNPs in codons 10, 325, 594, of estrogen receptor-α gene, in developing familial breast cancer. Therefore, ER-α and ER-β genotypes, as determined during pre-surgical evaluation, might represent a surrogate marker for predicting breast cancer in Iran.